Fraud Prevention in Accounting Students: The Impact of Using Anti-Fraud Awareness, Fraud Knowledge, and Religiosity - Hendardi Aryotama; Synthia Ferisca; Hendrian Yonata (Greenation Research & Yayasan Global Resarch National, 2026)
The purpose of this study is to determine how accounting students at one of Jakarta's universities apply their anti-fraud awareness, anti-fraud knowledge, and religiosity in relation to fraud prevention. In this inquiry, quantitative methodologies are employed. To sample the current population from various university cohorts of accounting students, random sampling is yet another technique employed. Using the criteria, 141 samples were eventually obtained. The SPSS is utilized in the data study process. As demonstrated by the study's findings, raising anti-fraud awareness considerably increases the possibility that fraud will not occur. Fraud expertise is quite beneficial when it comes to preventing fraud. Religion has a significant positive influence on avoiding fraud. Furthermore, how applying fraud knowledge, anti-fraud awareness, and religiosity simultaneously affects fraud prevention has effect significant.